Metodologia para análise da tarifa branca e da geração distribuída de pequeno porte nos consumidores residenciais de baixa tensão - Santos, Laura Lisiane Callai dos (2014)
This Master s Dissertation presents the development of a methodology that analyzes the impact of the White Tariff considering the distributed generation to low voltage residential consumers. The White Tariff has the aim of encouraging the reduction of energy consumption during the time of highest system load by consumers. Besides the low-voltage distributed generation aims the energy efficiency, the use of distributed generation and energy management by consumer. Considering this, the proposed methodology considers electricity tariffs, typical load curves ranged by consumption levels, natural resources and different of technologies for distributed generation. This database, combined with the software Hybrid Optimization Model for Electric Renewables (HOMER), presents as the main result the technical and economic feasibility for the use of distributed generation together with the white tariff, without changing the spending habits of consumers. The use of distributed generation is prioritized during the peak time, shifting the consumption from the electric power network to off-peak periods, where the white electricity tariff is shiper. The current costs of installation and operation of the distributed generation are high, but there is a tendency to their reduction due to an increase of its application and providers. It is emphasized that these analyzes, never seen before aim more efficient energy use of energy by both the application of white tariff and the encouragement to use of distributed generation.